2016
DOI: 10.1016/j.celrep.2016.03.079
|View full text |Cite
|
Sign up to set email alerts
|

KAT2B Is Required for Pancreatic Beta Cell Adaptation to Metabolic Stress by Controlling the Unfolded Protein Response

Abstract: The endoplasmic reticulum (ER) unfolded protein response (UPR(er)) pathway plays an important role in helping pancreatic β cells to adapt their cellular responses to environmental cues and metabolic stress. Although altered UPR(er) gene expression appears in rodent and human type 2 diabetic (T2D) islets, the underlying molecular mechanisms remain unknown. We show here that germline and β cell-specific disruption of the lysine acetyltransferase 2B (Kat2b) gene in mice leads to impaired insulin secretion and glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 47 publications
1
33
0
Order By: Relevance
“…HUANG_FOXA2_TARGETS_UP comprises 45 genes, some of which have been suggested to be implicated in the development of diabetes, such as KAT2B and TNFAIP3. Rabhi et al found that disruption of KAT2B led to impaired insulin secretion and glucose intolerance in mice [26]. They suggested that KAT2B was a key transcriptional regulator in maintaining normal function of adaptive β cell [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HUANG_FOXA2_TARGETS_UP comprises 45 genes, some of which have been suggested to be implicated in the development of diabetes, such as KAT2B and TNFAIP3. Rabhi et al found that disruption of KAT2B led to impaired insulin secretion and glucose intolerance in mice [26]. They suggested that KAT2B was a key transcriptional regulator in maintaining normal function of adaptive β cell [26].…”
Section: Discussionmentioning
confidence: 99%
“…Rabhi et al found that disruption of KAT2B led to impaired insulin secretion and glucose intolerance in mice [26]. They suggested that KAT2B was a key transcriptional regulator in maintaining normal function of adaptive β cell [26]. TNFAIP3 was suggested to be associated with type 1 diabetes [27].…”
Section: Discussionmentioning
confidence: 99%
“…During embryogenesis, GCN5 mRNA is already expressed at high levels by day 8, whereas KAT2b mRNA is first detected on day 12.5, suggesting that KAT2b and GCN5 play distinct roles by controlling the expression of a distinct set of genes ( 34 ). We have demonstrated that KAT2b is required for pancreatic β-cell adaptation to metabolic stress by promoting histone acetylation and gene expression of several unfolded protein response markers ( 35 ). While a β-cell-specific deletion of Kat2b in mouse has no effect under normal diet, Kat2b deficiency leads to a dramatic effect on β-cell morphology and function upon high fat feeding.…”
Section: Acetyl-coa and Histone/lysine Acetyltransferase Enzymesmentioning
confidence: 99%
“…While a β-cell-specific deletion of Kat2b in mouse has no effect under normal diet, Kat2b deficiency leads to a dramatic effect on β-cell morphology and function upon high fat feeding. KAT2b is thereby a major sensor of acetyl-CoA under hyperglycemic condition ( 35 ). Altogether, those data suggest that distinct histone acetyltransferases can sense acetyl-CoA upon different conditions and translate the appropriate cell response by activating different sets of genes.…”
Section: Acetyl-coa and Histone/lysine Acetyltransferase Enzymesmentioning
confidence: 99%
“…Further, Rabhi et al (2016) have identified a role for Lysine Acetyltransferase 2B (Kat2b) in the control of insulin secretion and pancreatic beta cell adaptation to metabolic stress through cellautonomous regulation of the UPR. This results in the induction of various ER chaperone, co-chaperone and ER-associated degradation genes after 24 h and an increase in pro-apoptotic genes (CHOP and Trib3) following 48 h of mutant insulin expression.…”
Section: Pancreatic Beta Cell Response To Er Stressmentioning
confidence: 99%